Participação de receptores serotoninérgicos e noradrenérgicos espinais no efeito antinociceptivo da corrente interferencial em modelo animal de inflamação articular - Carvalho, Maiara Simões (2019)
Introduction: The Interferential current (IC) is an electrotherapeutic modality widely used for analgesic purposes, however, few studies have sought to evaluate its mechanisms of action to promote the antinociceptive effect. The aim of this study was to investigate the involvement of spinal serotonergic and noradrenergic receptors in the antinociceptive effect of the interferential current in the animal model of articular inflammation in Wistar rats. Material and method: We included in this study 54 male Wistar rats distributed in the groups CI + saline, CI + DMSO 20%, inactive IC + saline, inactive IC + DMSO 20%, CI + methysergide, CI + tropanil dichlorobenzoate, CI + ioimbine, serotonin hydrochloride and hydrochloride of clonidine. At baseline, behavioral tests were performed for sensitivity and motor performance followed by induction of joint inflammation by injection of 3% carragein solution and 3% caolin in the left knee of the animals. After 24 h, the behavior was reevaluated followed by treatment with the current, preceded or not by pharmacological blockade. The pharmacological blockade was performed by means of intrathecal injection, applied before the treatment with the current. One hours after treatment with IC, the behavioral tests were repeated. The values of p < 0.05 were considered significant. Results: There was a significant decrease in the mechanical threshold of left paw withdrawal 24 h after the induction of inflammation in all groups (p < 0.0001). The groups treated with interferential current that received vehicles (saline or DMSO 20%) Significantly increased the mechanical threshold of paw withdrawal in comparison to the pre-treatment moment (p ≤ 0.001). Both with very large effect size according to Cohen's d (d = 1.95 and d = 1.83, respectively). There was blockade of the effect of IC in the groups that received, prior to the treatment with the current, the methysergide (non-selective antagonist of receptors 5-HT1 and 5-HT2) and tropanyl dichlorobenzoate (receptor antagonist 5-HT3). In these two groups, there was no statistically significant difference in the mechanical threshold of left paw withdrawal, when comparing the moments before and after treatment. In addition, after treatment, the pre-treated groups with methysergide or tropanyl dichlorobenzoate did not increase the mechanical threshold of left paw withdrawal, different from the vehicle groups. The animals that received yohimbine (α2-adrenergic antagonist) increased the mechanical threshold for the removal of the inflamed paw when comparing the pre-and post-treatment moments, showing that this pharmacological blockade did not prevent the effect of IC. Intrathecal injection of serotonergic and α2-adrenergic receptor agonists (serotonin hydrochloride and clonidine) significantly increased the mechanical threshold of left paw withdrawal (p ≤ 0.004). The distance traveled by the animals reduced significantly (p ≤ 0.0207) after the induction of inflammation, however, the administration of the drugs and/or treatment with IC did not exert influence on motor activity. Conclusion: This study shows part of the mechanism of action of IC in motor intensity to promote antinociceptive effect. This effect is mediated by spinal activation of 5-HT1, 5-HT2 and 5-HT3 receptors, but not α2-adrenergic receptors. These results allow professionals to justify the clinical indication of this electrotherapeutic resource, adapting its use to the physiopathological particularities of each individual.